A Note on Strong Convergence of Sums of Dependent Random Variables. (7th December 2009) - Hu, Tien-Chung; Weber, Neville C.
Abstract : For a sequence of dependent square-integrable random variables and a sequence of positive constants{ b n,    n ≥ 1 }, conditions are provided under which the series∑ i = 1 n ( X i − E X i ) / b i converges almost surely asn → ∞ . These conditions are weaker than those provided by Hu et al. (2008).